2017
DOI: 10.1021/acs.jproteome.7b00668
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Proteomic Alterations of F1 Capacitated Spermatozoa of Adult Mice Following Gestational Exposure to Bisphenol A

Abstract: Studies regarding bisphenol A (BPA) exposure and male (in)fertility have conventionally focused on modifications in ejaculated spermatozoa function from exposed individuals. However, mammalian spermatozoa are incapable of fertilization prior to achieving capacitation, the penultimate step in maturation. Therefore, it is necessary to investigate BPA-induced changes in capacitated spermatozoa and assess the consequences on subsequent fertilization. Here, we demonstrate the effect of gestational BPA exposure (50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…Thus, a 55 µm long spermatozoon efficiently covers 1000-3000 µm. During this journey, the morphology and chemotaxis of spermatozoa and ionic factors, protein phosphorylation (especially tyrosine), ATP, cyclic adenosine monophosphate, protein kinase-A (PKA), enzymatic factors, seminal plasma factors, and calcium ions present in spermatozoa play a dynamic role in keeping the spermatozoa motile (Kwon et al, 2014b;Rahman et al, 2017bRahman et al, , 2018. Simultaneously, certain fascinating physiological processes such as capacitation and the acrosome reaction occur in spermatozoa (Visconti, 2009;Battistone et al, 2013;Rahman et al, 2017b).…”
Section: Motility and Swimming Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a 55 µm long spermatozoon efficiently covers 1000-3000 µm. During this journey, the morphology and chemotaxis of spermatozoa and ionic factors, protein phosphorylation (especially tyrosine), ATP, cyclic adenosine monophosphate, protein kinase-A (PKA), enzymatic factors, seminal plasma factors, and calcium ions present in spermatozoa play a dynamic role in keeping the spermatozoa motile (Kwon et al, 2014b;Rahman et al, 2017bRahman et al, , 2018. Simultaneously, certain fascinating physiological processes such as capacitation and the acrosome reaction occur in spermatozoa (Visconti, 2009;Battistone et al, 2013;Rahman et al, 2017b).…”
Section: Motility and Swimming Patternmentioning
confidence: 99%
“…Identification and quantification of genes/proteins in a cell provides fascinating insights regarding their cellular functions. Genomics deals with the structure, function, evolution, and mapping of genomes (Bader et al, 2003), whereas proteomics involves novel approaches for characterizing proteins by performing qualitative and quantitative analyses (Rahman et al, 2016(Rahman et al, , 2017a(Rahman et al, , 2018. A spermatozoon provides half of the nuclear genetic material to the diploid offspring via fertilization.…”
Section: Genomic and Proteomic Contents Of X And Y Spermatozoamentioning
confidence: 99%
“…In additional, a significant increase in DNA damage to spermatocytes and decrease sperm count and motility was observed, following 12 weeks of BPA (10mg/kg bwt) administration in mice (44). Smilarly, Rahman et al (2017) reported that, toxic effect of gestational BPA exposure (5 mg/kg, and 50 mg/kg bw/day) on motility, capacitation, and motion kinematics of spermatozoa in mice. However, no or minimal effects were observed in the low-dose (50 µg/ kg) BPA group (45).…”
Section: Bpa Spermatogenesis and Sperm Qualitymentioning
confidence: 93%
“…Smilarly, Rahman et al (2017) reported that, toxic effect of gestational BPA exposure (5 mg/kg, and 50 mg/kg bw/day) on motility, capacitation, and motion kinematics of spermatozoa in mice. However, no or minimal effects were observed in the low-dose (50 µg/ kg) BPA group (45). Detrimental effects of BPA on sperm quality showed in experimental animal models has been confirmed by some studies conducted among groups of BPA-exposed human males (46).…”
Section: Bpa Spermatogenesis and Sperm Qualitymentioning
confidence: 99%
“…The comparable effect of EDs is known during spermatogenesis: BPA is capable of affecting meiotic division and chromosome segregation, increasing the incidence of aneuploidy-derived disorders [73]. In addition, the molecular mechanism of BPA consists in impacting several signal pathways and results in the change of protein kinase A activity and protein tyrosine phosphorylation, ATP generation, and oxidative stress-related enzymes (i.e., peroxiredoxin-5, glutathione peroxidase 4, succinate dehydrogenase), crucial for sperm motility and ability of oocyte fertilization [26,27,74]. Dose-response association of BPA and motility parameters of human sperm has been observed [75].…”
Section: Molecular Mechanism Of Eds In Extremely Low Dosesmentioning
confidence: 99%